Taking Open vSwitch to the Gym: An Automated Benchmarking Approach - Rosa, Raphael Vicente; Rothenberg, Christian Esteve (Anais do Workshop Pré-IETF (WPIETF), 2017)
Performance benchmarking in Network Function Virtualization (NFV) pose challenging issues due to all moving parts of virtualized infrastructures potentially affecting the packet processing performance of Virtualized Network Functions (VNFs). Despite the advances in best-of-breed network virtualization technologies, the dependencies on the underlying allocated hardware resources, their characteristics and customized configurations, result in benchmarking hazards that call for innovative and standardized testing methodologies towards adequate VNF performance profiling. To this end, we designed and prototyped Gym, a testing framework for automated NFV performance benchmarking we experimentally validated on Open vSwitch as a target VNF. The design principles and implementation of Gym demonstrate an useful apparatus to assist standards organizations formalizing VNF testing methodologies.